2018
DOI: 10.1136/tobaccocontrol-2017-054092
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of invehicle smoking and secondhand smoke exposure in Uruguay

Abstract: Smoking was estimated to occur in 12%-19% of vehicles, with involuntary exposure in one of three of vehicles observed. These data underscore a need for new public policies to eliminate SHS in vehicles to protect public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…With three cigarettes smoked, the front and back seat increases were 549 and 432 µg/m 3 , respectively. Multiple other studies confirm and discuss that air pollutants from car smoking rise above standards by the US EPA and WHO and produce several dangerous peak air pollution levels [25][26][27][28][29][30][31][32]. These levels are extreme enough to cause acute symptoms in children and, therefore, should prompt immediate steps to establish restrictions on smoking in cars with child/adolescent passengers.…”
Section: Discussionmentioning
confidence: 95%
“…With three cigarettes smoked, the front and back seat increases were 549 and 432 µg/m 3 , respectively. Multiple other studies confirm and discuss that air pollutants from car smoking rise above standards by the US EPA and WHO and produce several dangerous peak air pollution levels [25][26][27][28][29][30][31][32]. These levels are extreme enough to cause acute symptoms in children and, therefore, should prompt immediate steps to establish restrictions on smoking in cars with child/adolescent passengers.…”
Section: Discussionmentioning
confidence: 95%
“…The SILNE-R study on seven European cities found, for instance, that SHS exposure in cars on at least one day in the last week was reported, on average, by 22% of 14- to 17-year-old adolescents, while, in the German city of Hanover, 19% of this age group reported an identical prevalence [ 5 ], comparable to our study on the general German population. Additionally, across other high-income countries, approximately one fifth of youths [ 3 , 4 , 5 , 35 ] and adults [ 6 ] report SHS exposure in cars or at home [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondhand smoke (SHS) exposure in small, enclosed spaces has serious health effects (e.g., decreased lung function, asthma, persistent wheezing, sudden infant death) [ 1 , 2 ]. Currently, about 20% of adolescents [ 3 , 4 , 5 ] and adults [ 6 ] across high-income countries are exposed to SHS exposure in small, enclosed spaces such as cars or at their homes [ 7 ]. SHS exposure in indoor settings (e.g., in the private vehicle) is comparable to airborne concentration in indoor smoking bars, although atmospheric and biological markers of SHS concentration may be—in the case of private vehicles, for instance—mediated by the air conditioning, extent of airflow, and number of inches the windows are open [ 1 , 2 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…De acuerdo a un estudio reciente de nuestro equipo, en Uruguay, se estima que en 12% a 19% de los vehículos se fuma, y en un tercio existe otro individuo expuesto a HSM (15) . El reconocimiento de este problema y la obtención de datos objetivos sobre los niveles de concentración de HSM en autos servirán para impulsar la adopción de nuevas medidas de control de tabaco y a la autorregulación de la población en el cuidado de su salud, confiriéndole a este estudio relevancia tanto científica como social.…”
Section: Introductionunclassified